Morphological and morphometric comparisons of the first zoea of four species of purse crabs (Decapoda: Brachyura: Leucosiidae) from the Brazilian South Atlantic - Hirose, Gustavo L. [UNESP] (2012)
Morphological descriptions of the first larval stages of Persephona mediterranea, P. lichtensteinii and P. punctata (Leu-cosiidae: Eballinae) from the South Atlantic are provided, with comparisons among the morphometry of the species. A detailed description and eight morphometric measurements were made for each larva, and a discriminant function analysis was used to interpret the data set. The species differed significantly in certain morphological and morphometric features. These characteristics may help in the identification of species of Leucosioidea found in the South Atlantic, and can be an important tool in ecological studies, supporting the identification of planktonic morphotypes at the species level. © 2012 Magnolia Press.